THEOLOGICAL IMMUNITY AS AN EPISTEMIC STRATEGY: EMPIRICAL REFUTATION, DIVINE CAUSALITY, AND MYSTICAL AUTHORITY IN INDONESIA - Pikri, Zainal; Muthmainnah, Inna (UIN Raden Mas Said Surakarta, 2025)
This article examines an epistemological conflict at the intersection of empirical falsification and theologically grounded causal explanation. Focusing on publicly mediated debates in Indonesia between a medical science communicator and self-identified mystical practitioners (dukun), it analyzes how empirical challenges are deployed as instruments of epistemic adjudication. The study introduces the concept of theological immunity to explain why claims anchored in divine causality remain resistant to falsification. Rather than treating empirical non-performance as refutation, mystical practitioners reclassify failure through appeals to divine will, ritual propriety, or moral contingency. The analysis adopts an asymmetrical framework: Popperian falsifiability and methodological naturalism are treated as components of an epistemic regime that structures scientific challenge, while Islamic mystical epistemology (ʿilm al-ḥikmah) is examined on its own terms as a coherent theocentric causal ontology. Drawing selectively on Kuhn’s account of paradigm conflict and incommensurability, the article conceptualizes these encounters as clashes between epistemic regimes rather than disagreements within a shared paradigm. Empirical tests function as adjudicative mechanisms only within the naturalistic paradigm authorized by the scientific regime, but lose force across regimes grounded in incompatible ontological commitments. The result is an epistemic deadlock: refutation operates internally yet fails externally, highlighting the scope limits of falsifiability and clarifying why empirical testing cannot compel epistemic revision in claims rooted in divine causality.